Implementation of the Recitation Method in Learning Islamic Religious Education for Optimization Study Students on the Material of Reading the Quran and Morals at Al Maliky High School - Muhammad; Ilham; Irwan (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
Study This background behind by the lack of understanding student in the learning process teach so that result in they No Can finish problems given by the teacher as well lack of his participation part students in the learning process. This show indication to low results Study student in the learning process teaching. Research This is study qualitative. Deep data collection techniques study This that is observation, interviews and documentation. Observation used For collect data and view target research, methods interview used For know information about implementation method recitation in learning Islamic education? For optimization Study students on the material reading the Koran and Morals at Al Maliky High School. Based on results research that has been writer do, after the data is collected and analyzed so researchers conclude: Implementation method recitation in Islamic Religious Education learning at Al Maliky High School is carried out in two stages. First, the activity beginning, namely the teacher makes and prepares the lesson plan, second, the core activity, namely consists of from explanation material, in activity This, the teacher explains the material presented, next student given chance For ask, in activity this is also available stage evaluation, where the teacher gives task to student with share group For discuss material. Next, the teacher assesses results discussion. Stages furthermore is activity Finally, the teacher explains return material that has not been understood by students and provide in conclusion.